Novel polymerization catalysts and hydride clusters from rare-earth metal dialkyls - Nishiura, Masayoshi; Hou, Zhaomin (Nature chemistry, 2010)
Rare-earth metal dialkyl complexes can be readily transformed into the corresponding cationic monoalkyl species — which have been shown to catalyse a range of (co)polymerization processes — as well as into polyhydride complexes that have unique structures and a rich reaction chemistry. This Review gives an overview on recent progress in the synthesis and chemistry of rare-earth metal dialkyl complexes bearing monoanionic ancillary ligands, with an emphasis on novel polymerization catalysts. These structurally well-defined and highly reactive compounds are prepared either by alkane elimination reactions between trialkyl rare-earth complexes and acidic neutral ligands, or by the metathetical reactions of rare-earth trihalides with the alkali metal salts of the corresponding ligands. On treatment with an appropriate borate compound, the dialkyl complexes are converted into the corresponding cationic monoalkyl species, which serve as excellent catalysts for the polymerization and copolymerization of a variety of olefins to yield a series of new polymer materials that exhibit novel properties. Alternatively, hydrogenation of the dialkyl rare-earth complexes with H 2 affords a new class of rare-earth polyhydride complexes with unique features in terms of both their structure and reactivity.